Pancreatic exocrine responses to secretin, 2-deoxyglucose, a meal, and ethanol after coeliac ganglionectomy in the conscious dog. Issue 12 (December 1989) - Johnson, C D; Devaux, M A; Sarles, H
Abstract : The effects of coeliac ganglionectomy on pancreatic exocrine responses to graded doses of secretin, intravenous 2-deoxyglucose 100 mg/kg, ethanol 0.56 g/kg, and 1 g/kg, and to a meat meal were studied in conscious dogs (weight 11 to 27 kg). Five animals underwent coeliac ganglionectomy and up to seven control animals were studied. Coeliac ganglionectomy increased four-fold the pancreatic fluid response to secretin. The early part of the fluid response to 2-deoxyglucose was reduced, but there was no effect on the protein response to 2-deoxyglucose. In controls, ethanol 0.56 g/kg stimulated pancreatic secretion, to nearly double the basal level, but after coeliac ganglionectomy this dose of ethanol inhibited secretion to one third of basal values. There was no effect of coeliac ganglionectomy on pancreatic response to ethanol 1 g/kg. After coeliac ganglionectomy the early response to a meal was increased by 100% for fluid output and by 50% for protein secretion, but from 10 minutes to two hours after the meal there was no effect on pancreatic response. These data shed further light on the mode of action of ethanol on pancreatic secretion, and they indicate that therapeutic coeliac ganglia ablation in man is unlikely to be detrimental to physiological pancreatic secretion.